Pengembangan Sistem Informasi Peminjaman Ruangan Fakultas Kesehatan UDINUS Berbasis Web dan Mobile - wardoyo, agung (Universitas PGRI Semarang, 2025)
Currently, Management of room rentals at the Faculty of Health, Dian Nuswantoro University is currently still done manually, resulting in inefficient processes, potential schedule conflicts, and difficulties in tracking room availability. During the student and dean's deliberation activity, it was revealed that there were 24 complaints out of 30 complaints from students and student organizations regarding information on room availability for student activities. To overcome this problem, this study developed a Website and Mobile-based Room Rental Information System using the PHP Framework CodeIgniter (CI) for the website platform and Java with Android Studio for mobile applications. This system was designed with a prototyping approach and includes key features such as user authentication, calendar-based room rentals, automatic schedule validation, notifications, and administrative reports. Functional testing proved that the system runs according to user needs, reducing duplication of rentals. In the UIE (User Experience of interactive questionnaire) with 30 users, the Attractiveness, Perspicuity, Efficiency, Stimulation values of the alpha coefficient were above 0.7, which states that the website-based health faculty room loan information system is attractive, clear, efficient and provides an interesting experience.